Status związku (w związku intymnym vs singiel), konstrukt Ja i zdrowie psychiczne młodzieży akademickiej - Adamczyk, Katarzyna; Jankowiak, Barbara; Soroko, Emilia (Studia Edukacyjne, 2017)
The aim of this online survey was to test the hypothesis that self-construals (Independent self-construal and Interdependent self-construal) mediate the association between relationship status (single vs. partnered) and mental health. Four hundred and twenty-nine university students (327 females and 102 males) 19-25 (M = 21.79, SD = 1.72) completed the Polish versions of the General Health Questionnaire-28 and Self-Construal Scale. The results indicated that although different configurtions of self-construals are related to the level of experienced anxiety, the aspects of mental health analyzed are not related to the interaction between relationship status (partnered vs single) and 4 configurationsof self-construals. At the same time, the revealed lack of correlation between relationship status and mental health is contradictory to expectations and hypotheses. The results suggest that university students are perhaps in the middle of a prolonged moratorium, and in consequence, not making an attempt to fulfilldevelopmental tasks characteristic for (young) adults cannot be seen as an indicator of any aspect of psychological health.